2002
DOI: 10.1016/s0006-3495(02)75627-0
|View full text |Cite
|
Sign up to set email alerts
|

Computer Simulation of the 30-Nanometer Chromatin Fiber

Abstract: A new Monte Carlo model for the structure of chromatin is presented here. Based on our previous work on superhelical DNA and polynucleosomes, it reintegrates aspects of the "solenoid" and the "zig-zag" models. The DNA is modeled as a flexible elastic polymer chain, consisting of segments connected by elastic bending, torsional, and stretching springs. The electrostatic interaction between the DNA segments is described by the Debye-Hückel approximation. Nucleosome core particles are represented by oblate ellips… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
179
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(196 citation statements)
references
References 39 publications
17
179
0
Order By: Relevance
“…Thus, in the absence of imposed stretching forces, the fiber condensation at high salt concentration was induced by adjustment of a parameter, the decrease of the effective nucleosome diameter. In the study of chromatin folding by Langowski's group, the internucleosome interaction was described by a Gay-Berne potential, a generalization of Lennard-Jones potential for objects with ellipsoidal symmetry (34). However, their focus was on modeling chromatin at near-physiological ionic conditions; thus the effects of the ionic strength on the nucleosomal interactions and on the geometrical parameters were not modeled; it was suggested that reparameterizing the Gay-Berne potential according to the experimental salt-dependence of the linear mass density of the chromatin fiber is required to explore salt-dependent behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, in the absence of imposed stretching forces, the fiber condensation at high salt concentration was induced by adjustment of a parameter, the decrease of the effective nucleosome diameter. In the study of chromatin folding by Langowski's group, the internucleosome interaction was described by a Gay-Berne potential, a generalization of Lennard-Jones potential for objects with ellipsoidal symmetry (34). However, their focus was on modeling chromatin at near-physiological ionic conditions; thus the effects of the ionic strength on the nucleosomal interactions and on the geometrical parameters were not modeled; it was suggested that reparameterizing the Gay-Berne potential according to the experimental salt-dependence of the linear mass density of the chromatin fiber is required to explore salt-dependent behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the size and complexity of chromatin, computational studies have been based on coarse-grained models (29,(31)(32)(33)(34). For example, a dinucleosome was simulated on nucleosome-constrained circular DNA (31); strings of 4-24 nucleosomes were modeled by virtual bonds, and their structures were determined by geometric parameters (32); the nucleosome was represented by a spherical bead and the interaction between nucleosomes was modeled by a simple spherical isotropic steplike potential (29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Their systematic Monte Carlo simulations also support the notion that nucleosome interdigitation explains higher order chromatin structure and that the nucleosome repeat length affects the internal structure of the chromatin fiber. Other innovative modeling and simulation approaches for chromatin have explored various aspects of chromatin structure (21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…Hence modeling fiber structure and motion requires specialized models that treat the system's electrostatics as accurately as possible -since these features are thought to be crucial for chromatin organization -while approximating others so as to make possible studies of nucleosome arrays (or oligonucleosomes) with sufficient configurational sampling (e.g., 100 million configurations) or simulation times of milliseconds and longer to be biologically relevant. In recent years, a variety of computational models have been developed (e.g., [22,23,24,25,26,27,28]). …”
Section: Chromatin Structurementioning
confidence: 99%